Refractive outcomes following silicone oil tamponade in vitreoretinal surgery - Ramya Natarajan; Ashik Mohamed; Deepika C Parameswarappa; Padmaja Kumari Rani; Deepak Kumar Bagga; C Vijay Reena Durai (Oman Journal of Ophthalmology, 2024)
PURPOSE: To evaluate the factors influencing the refractive outcomes following silicone oil tamponade (SOT) and silicone oil removal (SOR) in different lens statuses post-vitreoretinal surgery. DESIGN: Retrospective analysis of three different lens statuses. MATERIALS AND METHODS: This was a descriptive study that included 150 eyes of 147 patients who had undergone pars plana vitrectomy with SOT and SOR between January 2017 and June 2021. Demographic profile, spherical equivalent refraction (SER), and its association with clinical features were evaluated with SOT and post-SOR. RESULTS: The mean (±standard deviation [SD]) age was 47 ± 17.8 years, including all three groups. SER was represented in diopters (D). The mean ± SD refraction with SOT in phakic, pseudophakic, and aphakic was 4.28 ± 2.59 D, 2.94 ± 2.58 D, and 3.98 ± 4.82 D. The mean SER post-SOR in phakic, pseudophakic, and aphakic was −2.72 ± 2.03 D, −1.12 ± 1.41 D, and 8.22 ± 3.70 D. The diagnosis of rhegmatogenous retinal detachment (RRD) among 96 eyes (64%) is the common indicator to perform vitreoretinal (VR) surgery. A minority of subjects were managed with retinal lasers before VR surgery (14%). The macula was attached in 100 eyes (67.6%), the belt buckle was done in 37 eyes (24.7%), and the silicone oil viscosity with 1000 centistoke was chosen in 129 eyes (86%). CONCLUSION: SOT was used as a tamponade in VR surgeries irrespective of lens status. The significant predictor for post-SOR refraction in phakic and aphakic is post-SOT refraction. In pseudophakic, gender and diagnosis of RRD are the predictors of SOR refraction.